Seeking social justice through globalization : escaping a nationalist perspective - Kitching, Gavin (Pennsylvania State University Press, 2001)
As demonstrations at meetings of world economic leaders have dramatically shown, the "globalization" of the world economy is now a subject of heated political debate. Generally supported for its positive benefits by neoliberals and attacked for its negative repercussions by the left, it is a multifaceted phenomenon, and even the term is much in dispute as both academic experts and political activists tend to define it in ways that best support their own biases. In this book, Gavin Kitching is not interested so much in providing new information about globalization as an economic and social process as he is in clarifying how globalization is to be understood and evaluated as a "good" or "bad" thing. Central to his argument is that a proper evaluation requires historical self-awareness, both of the historical background of globalization itself and of the historical origins of the very norms by which such evaluations are made. Unusual for a book written from a leftist perspective, Seeking Social Justice Through Globalization argues that those who care for social justice should seek more globalization, not try to prevent its development or roll it back. In his "modified Ricardian" analysis, Kitching warns especially about the constraints that the inherited discourse of economic and cultural nationalism places on the full potential of globalization to improve the welfare of poor people, which is his principal concern